The relationship between human resource management practices and job satisfaction: A case study among civil servants in Putrajaya - Anisah, Abas @ Hamdan (2014)
The purpose of this study was to determine the relationship between Human Resource Management (HRM) practices and job satisfaction among civil servants in Putrajaya, Malaysia. Four independent variables namely compensation, performance appraisal, training and development and career advancement have been selected for this study. The employees from a front liner agency in Putrajaya been selected as a target population. The survey was conducted using questionnaire and distributed randomly to the respondents. A total of 300 questionnaires were distributed and only 200 sets were returned and useable. Research findings revealed that there were a positive relationship between independent variables (HRM practices) and dependent variable (job satisfaction), however the regression analysis result indicate only three of the HRM practices namely compensation, performance appraisal and career advancement were significant with job satisfaction. Recommendations and implications for future research and practise have also discussed.